Analysis of the Cost Associated with the Treatment of Early Childhood Caries in Children Aged 2-6 Years - Pavithiraa Sankar1 , Deepa Gurunathan2 , Vignesh Ravindran3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
One cannot deny that cost factor plays an important role in the treatment phase of any disease and thus canwidely affect the patient’s acceptance to treatment. Overall cost of treatment gives an idea of the approximatecost differences that can be expected by patients. In this given study we aim to analyse the overall cost fortreatment procedures done for children suffering from early childhood caries in the state of Tamil Nadu. Thisis a hospital based retrospective study. All data of the patients visiting Saveetha Dental College and hospitalsfrom June 2019 to March 2020 located in Chennai were retrieved manually. Children who were diagnosedwith early childhood caries between 2-6 years who had at least one procedure done were included. A totalof 1210 patients were included in the study out of which 660 were males (54.55%), and 550 were females(46.45%). Out of 1210 patients: average costs for 1 to 5 procedures: Rs 231/-, 6 to 10 procedures: Rs 698/-,11 to 15 procedures: Rs 1222/-, 16 to 20 procedures: Rs 1783/-, 21 to 25 procedures: Rs 2419/-, 26 to 30procedures: Rs 2765/-, 31 to 35 procedures: Rs 3261/-, 36 to 40 procedures: Rs 3713/-, 41 to 45 procedures:Rs 3893/-. Out of total procedures the patient count for 1 to 5 procedures: 715, 6 to 10 procedures: 232,11 to 15 procedures: 98, 16 to 20 procedures: 47, 21 to 25 procedures: 40, 26 to 30 procedures: 30, 31 to35 procedures: 25, 36 to 40 procedures: 12, 41 to 45 procedures: 4. We can conclude that the most of thepatients required 1 - 5 dental procedures with the frequency being highest at 5 years and mostly in malechildren and the overall cost had a gradual linear increase with the increase in the number of procedures.